Picture and Picture Model Supports Better Mathematics Learning in Early Grades: Model Picture and Picture Mendukung Proses Belajar Matematika Lebih Baik di Kelas Awal - Celsy Okta Liski; Nurlev Avana; Dhini Mufthi (Academia Open, 2025)
Background: Low mathematics achievement among early-grade students is often linked to passive learning and limited use of interactive teaching media. Specific Background: Traditional approaches in SDN 109/II Dusun Mangis failed to engage students effectively in mathematical concept comprehension. Knowledge Gap: Few studies have examined the use of the Picture and Picture model in mathematics for first graders, despite its success in science and language subjects. Aim: This study aimed to improve students’ mathematics learning process and outcomes through the implementation of the Picture and Picture cooperative model. Results: Classroom Action Research was conducted in two cycles with planning, action, observation, and reflection phases. Results showed an increase in teacher performance (from sufficient to very good), higher student activeness (from low to highly active), and a significant rise in students meeting the minimum mastery criteria (from 64.29% in Cycle I to 92.86% in Cycle II). Novelty: This research provides empirical evidence for the use of Picture and Picture in mathematics at the early grade level, contributing to differentiated learning strategies. Implications: The findings encourage teachers to integrate visual and cooperative learning models to support active participation and improved learning outcomes in primary education. Highlight: Improved teacher performance and student activeness across cycles Higher number of students achieving minimum mastery criteria Visual-based learning supported conceptual understanding in early math learning Keyword: Picture and Picture, Mathematics Learning, Cooperative Learning, Student Activeness, Primary Education